Skopi: a simulation package for diffractive imaging of noncrystalline biomolecules. Issue 4 (16th July 2022) - Peck, Ariana; Chang, Hsing-Yin; Dujardin, Antoine; Ramalingam, Deeban; Uervirojnangkoorn, Monarin; Wang, Zhaoyou; Mancuso, Adrian; Poitevin, Frédéric; Yoon, Chun Hong
Abstract : The Skopi software package provides tools to generate realistic simulations of coherent X‐ray diffractive imaging of noncrystalline biological samples, which in turn will aid algorithm development for a range of experiments at X‐ray free‐electron laser sources. Abstract : X‐ray free‐electron lasers (XFELs) have the ability to produce ultra‐bright femtosecond X‐ray pulses for coherent diffraction imaging of biomolecules. While the development of methods and algorithms for macromolecular crystallography is now mature, XFEL experiments involving aerosolized or solvated biomolecular samples offer new challenges in terms of both experimental design and data processing. Skopi is a simulation package that can generate single‐hit diffraction images for reconstruction algorithms, multi‐hit diffraction images of aggregated particles for training machine learning classifiers using labeled data, diffraction images of randomly distributed particles for fluctuation X‐ray scattering algorithms, and diffraction images of reference and target particles for holographic reconstruction algorithms. Skopi is a resource to aid feasibility studies and advance the development of algorithms for noncrystalline experiments at XFEL facilities.